(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
HIV is a virus that attacks the immune system by infecting CD4 cells, damaging them and making the body more susceptible to opportunistic infections (OIs). Poor nutrition can exacerbate this issue by further weakening the immune system and increasing the risk of OIs. This study evaluated the nutritional status, dietary practices, and dietary management of people living with HIV/AIDS (PLWHA). A descriptive case study design was utilized, involving 194 HIV-infected individuals receiving treatment at General Hospital Kaura Namoda in Zamfara State. Anthropometric measurements were taken, blood samples were collected for biochemical analysis, and a semi-structured questionnaire was administered to assess the participants’ nutritional status. Among the participants, 59.8% were female, while 40.2% were male. The age distribution showed that 38.6% of the patients were between 30 and 39 years old, with 26.2% being female and 12.4% male. Additionally, 81.8% had attended school, while 18.2% had not. The survey revealed that 80% of the patients were married, and 74% were unemployed. Dietary intake analysis indicated that the consumption of macro- and micronutrients was inadequate compared to the Recommended Dietary Allowances (RDA). Body Mass Index (BMI) assessments showed that 46% of the PLWHA receiving treatment at General Hospital Kaura Namoda were underweight (BMI < 18 kg/m²). Also the result of the biochemical analysis indicated that serum albumin and total protein concentrations were significantly (p<0.05) lower in HIV-positive patients than in HIV-negative controls. These findings highlight the importance of proper dietary management for PLWHA to prevent malnutrition and associated complications. If not adequately...